Синтез подвійних фосфатофторидів лужних металів та нікелю (II) - Нагорний, П. Г.; Корнієнко, З.І.; Бойко, Р.С.; Городилова, Н.О.; Слободяник, М.С. (Видавничий дім "Академперіодика" НАН України, 2008)
Complex fluorophosphates of nickel and alkali elements M2NiPO4F (M = Li, Na) have been synthesized from flux melts of the system of fluorophosphates. The synthesis conditions and the existence area of synthesized phosphates are pointed out. The obtained compounds are investigated by X-ray FA, IR spectroscopy and quantitative analyses.